A New Prenylisoflavone from the Antifungal Extract of Leaves of Vatairea guianensis Aubl. - SOUZA, Ronilson Freitas de (Universidade Federal do Pará, 2017)
A new compound, 5,7,3'-trihydroxy-4'-methoxy-8-prenylisoflavone, was isolated from the leaves of Vatairea guianensis Aubl. (Fabaceae), together with two known isoflavones lupiwighteone and 5,7,4'-trihydroxy-3'-methoxy-8-prenylisoflavone. All isolated compounds were characterized based on infrared (IR), UV, 1H and 13C nuclear magnetic resonance (NMR), including 2D NMR analyses and high resolution mass spectrometry. The ethanolic extract from V. guianensis leaves displayed activity against Candida dubliniensis, C. albicans and C. krusei. However, the EtOAc fraction from that extract exhibited more significant activity than the ethanolic extract, showing antifungal activity for all fungi species investigated. The major compound 5,7,3'-trihydroxy-4'-methoxy-8-prenylisoflavone isolated from that EtOAc fraction was also active against C. parapsilosis and C. dubliniensis.